Development of Green Infrastructure on the Upper Board of the Citarum River Sector 6 - Sari Nurwulandari, Furi; Akil, Arifuddin; Syafri, Syafri; Manaf, Murshal (Department of Environmental Engineering - Universitas Pasundan - Indonesia, 2026)
Urban development in the Bandung Basin has exerted significant pressure on the function of the Citarum River Basin, particularly along riverbank areas. This study aims to examine the development of green infrastructure along the Upper Citarum River riparian zone in Sector 6 and to assess its integration with physical, social, and economic aspects of local communities. A qualitative descriptive method was employed through field observation and literature review. The study area, approximately 6 km in length, was divided into three segments based on land use characteristics and dominant activities. The results indicate that the implementation of green infrastructure along the Upper Citarum River in Sector 6 remains uneven. Segments 1 and 2 experience high pressure from land use activities, limited protective infrastructure, and greater vulnerability to flooding. In contrast, Segment 3 shows relatively better development, characterized by the presence of embankments and the utilization of riverbanks as public open spaces, although small-scale economic activities still pose potential threats to conservation functions. This study concludes that riparian management in the Upper Citarum River is still predominantly focused on physical interventions and has not fully integrated ecological, social, and economic functions. Strengthening green infrastructure-based riparian planning is therefore essential to support environmental sustainability and improve community quality of life.